Evaluation of the School Public Health Program in 61 Middle Schools in Sumbawa Regency - Has'ad Rahman Attamimi; Yunita Lestari; Ernawati Ernawati; Abdul Aziz (Jurnal Penelitian Pendidikan IPA, 2023)
This research aims to obtain an overview of the implementation of the UKS program. The subjects in this research were 61 junior high schools in Sumbawa Regency. Meanwhile, data collection techniques include observation techniques, in-depth interviews, and document study. For the evaluation model, the CIPP model is used. And data analysis is carried out interactively. The results of the evaluation based on the context component of the 61 schools evaluated, 46 stated that they were still experiencing difficulties in increasing prevention and resilience to the bad effects of narcotics, cigarettes, alcoholic drinks, and other dangerous drugs; then for the input component, there were still 37 schools that stated that UKS supervisors had not received training, while 19 schools stated that facilities were needed to be improved, and for the budget, 61 schools had a budget allocation; in the process component, at the planning and implementation stage all schools have program implementation plans, but at the monitoring and assessment stage this is not optimal; Meanwhile, for the Product component, no one has evaluated the impact of the UKS Program. It can be concluded that the implementation of UKS in 61 schools does not fully refer to the 2014 UKS implementation guidelines